Analyzing Migration Management: On the Recruitment of Nurses to Germany - Jan Kordes (Social Sciences, 2020)
In Germany, a grave labor shortage in the nursing and elderly care sectors has prompted the response of recruiting skilled nursing staff from abroad in recent years. This article analyzes these recruitment practices as forms of “migration management”: German migration policy has changed according to this paradigm to attempt utilitarian control over migration processes and mediate between labor market concerns on the one hand and isolationist, politico-cultural seclusion on the other. Based on original research through interviews and document analysis, we identify four relevant levels of analysis in researching migration management in the context of the recruitment of skilled nurses: (1) Definition of problem areas: How is migration programmatically legitimized as a solution to social problems? (2) Categorization of migration: How are migration processes classified? (3) Change in statehood: How are sites and actors of migration control being privatized and diversified? (4) Technologies: By means of which procedures, legal foundations and political instruments does migration management take place in the everyday? We believe that taking these four foci as points of departure would be beneficial for further inquiries in critical migration research.